MACAM-MACAM KARAKTER TOKOH UTAMA DALAM NOVEL BANDIT BANDIT BERKELAS KARYA TERE LIYE - Teuku Arif Andika; Hasmi Suyuthi; Elyusra Elyusra; Ira Yuniati (LPPM Universitas Bina Bangsa, 2025)
This study examines the character education values portrayed in the main characters of the novel Bandit Bandit Berkelas by Tere Liye. The objective of this research is to identify and analyze in detail the character education values embedded by the author in the depiction of the main characters. The significance of this study is twofold: theoretically, it is expected to contribute to the understanding of character education values in literary works, particularly in this novel, and to support the development of literary studies; practically, the findings may benefit readers, students, and future researchers interested in literary analysis and character education. The data used in this study consist of quotations from the novel that reflect character education values. The data collection technique employed is library research. The results show that there are 100 data points representing character education values found in the main characters, covering 9 different types of values. Additionally, there are 9 other character values that are not reflected in the novel, as a thorough reading of the work revealed that these values were not portrayed by any characters